Pengaruh Media Pembelajaran Google Sites terhadap Literasi Sains pada Suhu dan Kalor - Syahidah Syahidah; Maya Istyadji; Rizky Febriyani Putri (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2026)
Scientific literacy is an essential competency through which students are able to comprehend scientific concepts and apply them in everyday life. This study aimed to investigate how Google Sites learning media influences students' scientific literacy in the topic of heat and temperature. Quasi-experimental approach with a Nonequivalent Control Group Design was employed in this study. Participants included of 68 seven-grade students from SMP Negeri 31 Banjarmasin and were assigned to experimental group and a control group. Scientific literacy tests and student response questionnaires were used to colled the data, which were analyzed using descriptive statistics, the N-Gain analysis, prerequisite testing, and the Independent Samples t-test. The finding showed that students who learned through Google Sites significantly higher scientific literacy compared with conventional learning methods. Additionally, studentsexpressed very positive responses toward the implementation of the learning media. Therefore, Google Sites learning mediais effective inm improving students' scientific literacy in science learning.